Effects of individual characteristics on expatriates' adjustment and job performance - Bhatti, Muhammad Awais; Kaur, Sharan; Battour, Mohamed Mohamed (Emerald Group Publishing Limited, 2013)
Purpose– Researchers have been focusing on the predictors of expatriates' adjustment and job performance at different levels (individual level, organizational level and societal level), but still some of the predictors have been ignored or unclear in the expatriate literature. The purpose of this paper is to develop a comprehensive framework in order to better understand the role of individual factors in expatriate adjustment and job performance.Design/methodology/approach – The review of past research is used to develop a conceptual framework.Findings – This conceptual paper provides theoretical ground for individual factors which include Big Five, self‐efficacy, previous international experience, cultural sensitivity and social network and proposes that expatriate adjustment (work, general and interaction adjustment) mediates the relationship between individual factors (personality traits (Big Five), self‐efficacy, previous international experience, cultural sensitivity and social network) and expatriate job performance (rated by peer and supervisor).Practical implications– This paper also provides practical implications for the managers and professionals involved in expatriates' selection, training and performance management.This paper suggests that managers involved in selection of candidates for international assignment should consider personality traits, level of self‐efficacy, previous international experience, social network and cultural sensitivity at the time of selection of candidates for international assignment. Furthermore, managers should design pre‐departure training programs in a way that enhances candidates' self‐efficacy level, overcomes cultural sensitivity, and motivates them to expand social network. Finally, managers should explain to the candidates how they can use their personal skills and knowledge to gain work, general and interactions adjustment in order to achieve job tasks.Originality/value– The proposed framework is developed based on the past theoretical review in order to cover the gap and contribute to the body of knowledge in expatriate literature.Based on the proposed framework, this paper invites researchers to empirically test the suggested propositions in order to further strengthen and develop understanding about individual factors including Big Five and other expatriates' adjustment and job performance predictors.